Urban Health Resilience: Strategies for Strengthening Public Health Systems in Response to Urbanization Challenges - Medha Mathur; Varun J. Wani; Rivu Basu; Priya Manihar; Mohammad Waseem Faraz Ansari; Navgeet Mathur; Shaili Vyas; Smrutiranjan Nayak; Anjana Verma; Surendra Singh (Indian Journal of Community Medicine)
The social structure of India is rapidly evolving, towards modernization. The urban population of India is projected to approach 60 crores by 2036. Urban health resilience stands for building the capacity of urban systems to withstand and adapt to health-related stresses like natural disasters, man-made disasters, and pandemics like COVID-19 and the capability to recover from them by well-equipped hospitals, efficient emergency response mechanisms, and a network of well-trained and motivated healthcare professionals. Also, the involvement of communities is central to building urban health resilience. Strong policy frameworks are required for establishing a resilient urban health ecosystem. Addressing social determinants, such as income inequality, education, and housing, is also a basis of building urban health resilience. Some examples have been instrumental in designing a resilient urban health system like Singapore’s Smart Nation Initiative, Copenhagen, Denmark’s Model for Sustainable Urban Living internationally, Ahmedabad’s Heat Action Plan and Kochi’s Waterfront Development for Climate Resilience are excellent examples from our country. The suggested strategy for an urban resilient system is a Rapid, Extensive, Sturdy, Ingenious, Lucid approach with an International collaboration for an Enthusiastic, Non-latent, Continuous Early warning system (RESILIENCE).